PEMBERIAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) PADA PEMBIBITAN UTAMA - Kardi ' Yanto; Adiwirman ' '; Nurbaiti ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aimed to determine the effect of organic liquid fertilizer and liquid organic fertilizer obtain a concentration corresponding to the growth of seedlings of oil palm (Elaeis guineensis Jacq). The main breeding and looking for correlations of all parameters in the treatment gives the highest influence on the main nursery. Completely randomized design (CRD), consisting of 5 treatments with 4 replications. Data were  analyzed by analysis of variance, HSD (Honestly Significant Difference) at 5% level and correlation was used in this research. The parameters were observed in the study were plant height increment, the increase in diameter stump, in the number of leaves, root volume, fresh weight and dry weight. Liquid organic fertilizer significantly affects on plant height increment parameter, the increase in diameter stump, root volume, fresh weight and dry weight of oil palm seedlings, but no significant difference in the parameter number of leaves. Organic fertilizer at a concentration of 6 ml / l of water showed the highest value on each parameter observation that a high increment of plants, increase the diameter of the pulpit, in the number of leaves, root volume, fresh weight and dry weight of oil palm seedlings than other concentration.   Keywords : organic liquid fertilizer, palm oil, concentration